Meta-analysis: The Effectiveness of Using Socio-scientific Issues on Science Literacy and Students' Higher-Order Thinking Ability in Science Learning - Zulyusri Zulyusri; Asra Indah; Tomi Apra Santosa (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
This study aims to determine the effectiveness of the use of socio-scientific issues on scientific literacy and higher order thinking skills of students in science learning. This research is a type of meta-analysis research. This research data comes from the analysis of 20 national or international journals that have been published from 2016-2022. The search for data sources comes from the Google Scholar, Eric Journal, ScienceDirect, and Springer databases. The sampling technique is purposive sampling technique. The data that is used as a sample must know the criteria that have a relationship with the research variables, namely social science on scientific literacy and students' higher order thinking skills in science learning. Data analysis is a quantitative data analysis technique with the help of JSAP.. The results of the study indicate that the use of socio-scientific issues affects students' higher order thinking skills by 47% and scientific literacy by 53% with an n-Gain of 0.50 medium category. This shows that the use of socio-scientific issues in science learning has a significant effect on students' higher-order thinking skills and scientific literacy.